SCS-ESP: Self-Value Excellence Programme on 26th-28th August 2016 at Damai Beach Resort Kuching - Amalia, Madihie (2016, 2016)
Self-Value Excellence Module is written by a group of subject experts in counseling and psychology led by Amalia Madihie PhD from Universiti Malaysia Sarawak. The module is based on the 6 Shared Values of the State of Sarawak Government as foundation to achieve vision ~ A world class civil service. Choice Theory is applied as theoretical framework in developing the module and a standard of module development model is implemented too. Self-Value Excellence Module won Silver Medal at the INTEX UNIMAS 2016 in Mac this year. Below is the subject matters: